Leishmania infantum infecting the carnivore Nasua nasua from urban forest fragments in an endemic area of visceral leishmaniasis in Brazilian Midwest - de Macedo, Gabriel Carvalho; Barreto, Wanessa Teixeira Gomes; de Oliveira, Carina Elisei; Santos, Filipe Martins; Porfírio, Grasiela Edith de Oliveira; Xavier, Samanta Cristina das Chagas; Alves, Fernanda Moreira; da Silva, Alanderson Rodrigues; de Andrade, Gisele Braziliano; Rucco, Andreza Castro; de Assis, William Oliveira; Jansen, Ana Maria; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction The aim of the present study was to investigate the occurrence of Leishmania infantum in South American coatis inhabiting two forest fragments in Campo Grande, Mato Grosso do Sul, Midwest region of Brazil, an endemic area of human and canine visceral leishmaniasis (VL). Material and methods A total of 110 South American coatis were sampled in the conservation unit “Parque Estadual do Prosa” (PEP) and in the residential area “Vila da Base Aérea” (VBA) from March 2018 to April 2019. As a longitudinal study that include up to six recaptures of the same individual, a total of 190 capture events were obtained. Blood, bone marrow and skin samples were obtained for parasitological (axenic culture), serological (Enzyme Linked Immunosorbent Assay – ELISA and Dual-path Platform immunoassay – DPP® CVL) and molecular diagnostic assays (targeting kDNA for Leishmania spp. and L. infantum; and HSP70 followed by sequence analysis). Results Seropositivity for L. infantum was found in 33 individuals, six in PEP and 27 in VBA. Furthermore, L. infantum was detected by molecular analysis in 16 individuals, seven from PEP and nine from VBA. We also isolated L. infantum from bone marrow of one individual and detected a single positive skin sample in molecular assay from other individual, both from VBA. Discussion An overall infection rate of 36.4% (40/110) was observed, significantly higher in the VBA (49.1%) than in the PEP (21.6%), probably because VBA presents: (i) a large number of resident dogs and chickens that would be attracting sandflies; (ii) a denser population of this wild mammal species; and (iii) physical barriers and a lack of functional connectivity in the surroundings, preventing these animals to disperse out. We conclude that South American coati populations living in urban forest fragments of Campo Grande are affected by the epidemiological scenario of VL, known to involve dogs, vectors and humans. We highlight the importance of investigate the parasitism by L. infantum in this and other potential L. infantum reservoirs that inhabit urbanized regions endemic to VL.